P3.218 Demographic and clinical profiles of women with bacterial vaginosis and sexually transmitted infections: implications for the management of vaginal discharge syndrome in south africa. (8th July 2017) - Chakezha, Tendesayi; Gumede, Lindy; Maseko, Venessa; Radebe, Frans; Kularatne, Ranmini
Abstract : Introduction: Current South African syndromic management guidelines for vaginal discharge syndrome (VDS), recommend only metronidazole and clotrimazole therapy for women 35 years or older, whose partners have no urethral discharge. This guidance assumes the older women have bacterial vaginosis or candidiasis without STIs and that their partners are not asymptomatic. We describe demographic, behavioural and clinical characteristics of women with VDS comparing those with BV and candida to those infected with STI pathogens. Methods: Cross sectional study, in which women≥18 years presenting with VDS to five primary healthcare centres between January 2015 - September 2016 were enrolled. Demographic and clinical data were collected using a nurse-administered questionnaire. Vaginal smears, endocervical swabd and venous blood specimens were collected for laboratory testing. Presence of BV in the genital specimens was assessed using Gram stain smear and Nugent scoring while that of Candida was assessed using microscopy. In-house multiplex PCR was used to detect the following STI pathogens – Neisseria gonorrhoeae (NG), Chlamydia trachomatis (CT), Trichomonas vaginalis (CT ) and Mycoplasma genitalium (MG) . HIV positivity was determined using commercial rapid tests.Data was captured into a Microsoft Access 2010 database and exported into Stata 14 for analysis using descriptive statistics, comparing four groups Group 1- women with BV or Candida infection only, Group 2 – women with BV or Candida with an STI, Group 3 – women with an STI infection only and Group 4 – women with no pathogens detected in the laboratory. Results A total of 771 women – median age 27 years [interquartile range (IQR) 23–32 years], 140 (19.5%) ≥35 years and 326 (45.4%) HIV positive- were enrolled. Of these: 253 (35.3%) were in Group 1, 238 (33.2%) in Group 2, 99 (13.8%) in Group 3, and 127 (17.7%) in Group 4. The proportions of women who were 35 years or older were 20.2%, 13.9%, 19.2% and 29.1% in Groups 1, 2, 3 and 4 respectively (p=0.006) while the HIV positivity was 43.1%, 55.9%, 43.4% and 32.3% in the groups (p<0.001). Condom use at last sexual encounter was 24.6%, 16.6%, 19.4% and 16.8% in Groups 1, 2, 3 and 4 respectively. The groups were similar in other respects although women in Group 2 had significantly higher rates of CT compared to Group 3. Conclusion: There were smaller but significant proportions of women 35 years or older had STIs with or without BV or Candida. The use of this age-specific threshold to guide syndromic treatment should be reconsidered, and HIV/STI integration promoted for women with VDS. Support: : The Centre for HIV and STIs at National Institute of Communicable Diseases in South Africa is funded by the South Africa's National Department of Health. No pharmaceutical grants were received in the development of this study.